octanate®: over 20 years of clinical experience in overcoming challenges in haemophilia A treatment - Klukowska, Anna; Komrska, Vladimír; Vdovin, Vladimír; Zozulya, Nadezhda; Lissitchkov, Toshko; Oldenburg, Johannes; Ettingshausen, Carmen Escuriola (Therapeutic advances in hematology, 2020)
Treatment of haemophilia A with FVIII replacement has evolved over the past decades to adapt to the needs of patients. octanate®, a plasma-derived, double virus-inactivated, von Willebrand factor (VWF)-containing FVIII concentrate, has been used in clinics worldwide for over 20 years. First licensed in 1998 in Germany, octanate® is approved in over 80 countries for the prevention and treatment of bleeding and for surgical prophylaxis in patients with haemophilia A, and in over 40 countries for immune tolerance induction (ITI). The manufacturing process for octanate® was developed to ensure high viral safety and effectively eliminates both enveloped and nonenveloped viruses. Over the past 20 years, the excellent safety and efficacy of octanate® have been demonstrated in pivotal clinical trials in adult and paediatric previously treated patients (PTPs) for on-demand treatment, prophylaxis and as surgical cover. Importantly, octanate® has displayed low immunogenicity in previously untreated patients (PUPs), with only 9.8% of PUPs developing FVIII inhibitors. octanate® has also shown to be highly effective in inhibitor elimination when used as ITI therapy. In a population of patients with high risk of ITI failure, success was achieved in 79.2% of patients (70.8% complete success), even when using exceptionally stringent success criteria. No relapses were observed. Here we present an overview of the clinical data with octanate® that support its use in a range of patient populations and clinical indications.